PENGARUH PELAYANAN FISKUS, KONDISI KEUANGAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK (Studi Kasus terhadap Wajib Pajak Orang Pribadi di Kabupaten Temanggung) (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of the service tax authorities, financial condition and sanctions against the tax compliance rate individual taxpayers in Temanggung Regency.The population in this study were all individual taxpayer who resides in Temanggung Regency, while the samples taken are an individual taxpayer whose income is fixed, has a tax number and resides in Temanggung Regency. The type of data in this study using primary data is data collected specifically and directly related to the problems with the researchers took a sample of 80 respondents. The data is then tested the normality test, the classical assumption of multicollinearity test and test heterokedastisitas with multiple linear regression analyzes.The results of the data is normally distributed and free from symptoms of classical assumptions. Tests carried out by F test models and koefisient determination, whereas hypothesis testing performed by t test (test). Based on data analysis and hypothesis testing shows that the service tax authorities and tax penalties significant and positive impact on the level of compliance of individual taxpayers in Temanggung Regrency, while the taxpayer's financial condition was not significant and negative effect on the level of compliance of individual taxpayers in Temanggung Regency.Keywords: Level of Compliance Tax, Service tax authorities, Taxpayer Financial Condition and Tax Penalties